Effect of cigarette smoking on nasal mucociliary clearance and ciliary beat frequency. - Stanley, P J (1986)
Despite the in vitro ciliotoxicity of tobacco smoke and the abnormal mucociliary clearance found in smoking related chronic bronchitis, studies of mucociliary clearance in healthy smokers have produced variable results. The nasal mucociliary clearance of saccharin and the in vitro nasal ciliary beat frequency were studied in healthy smokers and non-smokers. One of 29 smokers had a nasal mucociliary clearance time of over 60 minutes; in the remaining 28 the mean (SD) clearance time was 20.8 (9.3) minutes, which was significantly longer (p less than 0.001) than the mean time of 11.1 (3.8) minutes in 27 lifelong non-smokers. There was no significant difference between the mean nasal ciliary beat frequency of 10 smokers and 10 non-smokers. There were no significant differences in mean ciliary beat frequency or mean nasal mucociliary clearance time after 10 healthy non-smoking volunteers had smoked two cigarettes each, exhaling the smoke through their nostrils. Unless there is a prompt reversal of any ciliotoxic effect of tobacco smoke when cilia are removed for in vitro examination, the defective clearance seen in chronic cigarette smokers seems unlikely to be due to slowed ciliary beat frequency. It may be due to reduction in number of cilia or to change in the viscoelastic properties of mucus. The failure to detect any acute effect of tobacco smoke is in keeping with this hypothesis.